Inflammasomes: Caspase-1-Activating Platforms with Critical Roles in Host Defense - Vande Walle, Lieselotte; Lamkanfi, Mohamed (Frontiers in Microbiology, 2011)
Activation of the inflammatory cysteine protease caspase-1 in inflammasome complexes plays a critical role in the host response to microbial infections. Inflammasome activation induces inflammation through secretion of the pro-inflammatory cytokines interleukin (IL)-1β and IL-18 and through extracellular release of the alarmin HMGB1. Moreover, caspase-1 activation by inflammasomes counters bacterial replication and induces pyroptosis, a specialized cell death program that removes infected immune cells as part of the host defense system. It is thus not surprising that bacterial and viral pathogens evolved virulence factors targeting inflammasome activation and activity. Here, we provide an overview of the distinct inflammasome complexes that are activated in a pathogen-specific manner and discuss the diverse strategies employed by viruses and bacteria to modulate inflammasome function.